Analisis Dan Perancangan Filter Pasif Untuk Mereduksi Pengaruh Harmonisa Pada Inverter 3-Fasa Menggunakan Matlab/Simulink - Saputro, Devy Bagus, Ir. Jatmiko, M.T (2017)
The inverter is a power electronics circuit used to convert direct current (DC) into alternating current (AC). The use of 3-phase inverter on the power grid can cause a defect harmonics that will impact on the voltage and current waves. One solution to reduce the effects of harmonics is to install passive LC filter. The design and installation of passive filter is simulated by using software MATLAB Simulink R2010b so that the result values for Total Harmonic Distortion (THD). THDv arising from the current system before passive harmonic filter installed on phase R = 52.29%, phase S = 52.24%, and phase T = 52.03%. Once installed passive filter which in this study using a type tunned filter capable of reducing THDv the R phase becomes 3.23%, phase S = 3.13%, and phase T = 3.24%. The simulation results were telahHasil simulations have been done installing passive LC filter capable of reducing THDv system in accordance with IEEE standard 519-1992.